5 - Junior Academics within Middle Level Academic Leadership in Emerging Universities in Nigeria - Omotosho, Babatunde Joshua (Journal of Higher Education in Africa, 2022)
One of the emerging developments within middle level academic leadership in Nigerian universities relates to the inclusion of academics who are at the very beginning of their careers within middle level leadership. The term junior academics is used here to refer to academics who are on staff development terms, registered for doctoral studies, or just graduated from doctoral studies and starting the process of being socialized into institutional academic cultures. In most emerging (3rdgeneration) universities, such academics are often allocated academic and administrative roles that would otherwise be performed by middle level academics in well-established universities. This trend, occurring majorly among emerging universities, appears to be a response to the dearth of middle level academics to occupy middle level leadership positions. While this development appears to serve as an emergent response to the challenges on hand, the implications on middle level academic leadership, university administration and governance as a whole need to be critically explored. This article interrogates on how junior academics serving within middle level leadership came to be, implications on university leadership, and finally a conclusion on how this challenge can be addressed to pave the way for effective middle level academic leadership within university administration.